Introduction to the American Criminal Justice System - Burke, Alison S.; Carter, David E.; Fedorek, Brian; Morey, Tiffany L.; Rutz-Burri, Lore; Sanchez, Shanell; Open Textbook Library (Open Textbook Library, 2019)
There is a dearth of OER textbooks in Criminology and Criminal Justice, which made creating this textbook all the more exciting. At times we faced challenges about what or how much to cover, but our primary goal was to make sure this book was as in-depth as the two textbooks we were currently using for our CCJ 230 introduction course. The only way we were willing to undertake this project as if it was as good, or better than the current books students read. We have had very positive feedback about the required textbooks in the course but consistently heard how expensive the books were to buy. We also needed to ensure we met the learning outcomes outlined by SOU for a general education course, as well as the state of Oregon, to make sure this textbook helps students meet those outcomes.
1: Crime, Criminal Justice, and Criminology -- 2: Defining and Measuring Crime and Criminal Justice -- 3: Criminal Law -- 4: Criminal Justice Policy -- 5: Criminological Theory -- 6: Policing -- 7: Courts -- 8: Corrections -- 9: Community Corrections -- 10: Juvenile Justice
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Criminal Law -- Textbooks